Analisis Kesehatan Kinerja Realisasi APBDesa di Wilayah Kapanewon Karangmojo Kabupaten Gunung Kidul Tahun 2018-2022 - Wibisono, Diaz Wisang; Prihatni, Rida; Perdana, Petrolis Nusa (LPPM Universitas Negeri Jakarta, 2024)
This research aims to determine and analyze the health and financial performance of the village government in the Kapanewon Karangmojo area, Gunung Kidul Regency in the 2018-2022 budget period. This research uses various financial ratios that are useful for measuring financial performance, namely the Degree of Decentralization Ratio, Financial Independence Ratio, Efficiency Ratio and Effectiveness Ratio, and this research adds income growth, both village original income and Total Income growth. This research is a type of quantitative descriptive research using secondary data in the form of the Village Government Revenue and Expenditure Budget Realization Report (APBDes) in the Kapanewon Karangmojo area, Gunung Kidul Regency for the 2018-2022 budget period. the Financial Performance of the Village Government in the Kapanewon Karangmojo Region, Gunung Kidul Regency based on the Degree of Decentralization Ratio has a very low level of capability, the Financial Independence Ratio has a very low level of independence and has an Instructive relationship, the Efficiency Ratio results in five villages being declared less efficient and two villages received information about being inefficient.